Prevalence and risk factors of chronic diseases of lifestyles in endurance runners - Language, Sarah (Division of Physiotherapy, 2019)
Background: Chronic diseases of lifestyle (CDL) are associated with high rates of morbidity and mortality in South Africa. Although prevalence of CDL has been established in the general population, there is limited research regarding the prevalence and risk factors for CDL in individuals taking part in regular physical activity. Endurance running is a popular sport, with growing levels of participation. Anecdotally, many individuals who participate in endurance running do not undergo formal pre-participation cardiovascular screening. It is also unclear if endurance runners are meeting the World Health Organisation’s recommended weekly moderate to vigorous intensity physical activity hours, or if they have other risk factors for CDL. It is therefore important to establish the prevalence and risk factors of CDL in this active population. Aim and Objectives: The aim of this study was to determine the prevalence of CDL and the associated risk factors in endurance runners in South Africa. The specific objectives of the study were: (a) to determine the presence of risk factors for the development of chronic diseases of lifestyle, including body mass index (BMI), waist circumference, body fat percentage, blood pressure, blood glucose, blood cholesterol, smoking history, dietary intake and weekly physical activity time in South African endurance runners; (b) to determine the presence of non-modifiable risk factors to the development of CDL, namely age and income, in South African endurance runners; (c) to determine whether South African endurance runners are fulfilling the World Health Organization’s recommended weekly moderate to vigorous intensity physical activity hours; and (d) to assess whether there are any relationships between the running characteristics, namely weekly training hours, running speed and level of competition; and the risk factors for chronic diseases of lifestyle. Methods: This study had an analytical, cross-sectional design. Two hundred participants between the ages of 18 to 69 years old, who reported endurance running as their main sport, and ran at least three kilometres twice a week for the past year were included in the study. Participants were excluded if they were pregnant or within six months post-partum, had an injury that required a minimum of two weeks rest or did not complete the questionnaire or physical testing component of the testing process. Participants were recruited through local running clubs and running races in the areas of Nelspruit, Mpumalanga and Cape Town, Western Cape. All participants gave written informed consent, and completed a questionnaire including socio-demographic characteristics, running training characteristics, the International Physical Activity Questionnaire short questionnaire, the modified Borg scale of perceived exertion, and the five-a-day community evaluation tool. Body mass, stature, skin folds and waist circumference were assessed. Blood pressure was measured using an automatic blood pressure monitor. A finger prick test was used to determine random blood glucose and cholesterol concentrations. Participants were requested to fast for three hours prior to testing to standardise the test in a non-fasted state (20). Results: One hundred and twenty four (62%) participants were found to have at least one risk factor for CDL. A high BMI was the most common risk factor for CDL (n=90; 45%). Nineteen participants (9.5%) did not meet the recommended duration of 150 minutes of physical activity per week. Seven percent of female participants (n=7) smoked, which is equivalent to the female population average of South Africa. Multiple risk factors were identified in fifty seven (28.5%) participants, ranging from two risk factors (n=37; 18.5%) to six risk factors (n=1; 0.5%). The majority of participants had no prior medical diagnosis of CDL or risk factors for CDL. The overall self-reported prevalence of a medically diagnosed CDL was 5.5% (n=11). Type 2 diabetes was the most commonly diagnosed CDL (n=6; 3%). Waist circumference, systolic blood pressure and cholesterol were significantly elevated in the older age group. There were no significant differences in risk factors for CDL according to income status. Female runners had significantly higher average sitting times compared to male runners. In addition, participants with a BMI ≥ 25 kg.m-2 had significantly slower 10 km running speeds and lower average weekly training distance, compared to participants with BMI within normal ranges. Conclusion: A high prevalence of risk factors for CDL was identified in South African endurance runners. The majority of endurance runners included in this sample are fulfilling the World Health Organisation’s recommended weekly moderate to vigorous intensity hours. However, the endurance runners in this study remain at risk for developing a CDL due to the presence of other risk factors for CDL. The knowledge and awareness of risk factors for CDL among South African endurance runners needs to be further investigated. Health care professionals are required to improve the prevention and management of risk factors of CDL through education and promotion of healthy lifestyles. A stronger emphasis on the prevention of risk factors for CDL in South African endurance runners is needed.